Comparison of Facial Soft Tissue among Different Facial Patterns: A Cephalometric Study - Yadav, Rajiv; Yadav, Neelam (Journal of Institute of Medicine Nepal, 2024)
Introduction With the advancement of the soft tissue paradigm, various soft tissue factors have been added to the orthodontic problem list for diagnosis and treatment planning. This study aimed to examine the dimensions of facial soft tissues alongside various cephalometric parameters in orthodontic patients. Methods This observational study was conducted at Department of Orthodontics and Dentofacial Orthopedics, Dental Clinical Sciences-1, TU Teaching Hospital. Three different groups based on the morphological patterns (brachyfacial, dolichofacial, and mesofacial) with soft tissue parameters of upper lip thickness (ULT), lower lip thickness (LLT), upper lip height (ULH), lower lip height (LLH), soft tissue chin thickness (SCT) were studied. X-rays selected for this study from 18-30 years old patients with no craniofacial deformities were selected. SPSS 21 was used for statistical analysis. Results The mean value of facial axis measurement (BaN.PtGn) was 90.02±4.140. The mean values of ULT was 14.51±2.74 mm, LLT was 16.33±1.87 mm, ULH was 28.21±3.66 mm, LLH was 47.43±4.66 mm, and SCT was 14.70±2.54 mm. The BaN.PtGn, ULT, and SCT were significantly different among three facial types. Brachyfacial facial type had higher ULT than mesofacial and dolichofacial types whereas higher SCT than mesofacial types. The correlation between different soft tissue measurements showed weak to very weak strength association. Conclusions Brachyfacial facial types had higher upper lip thickness than mesofacial and dolichofacial types and higher soft chin thickness than mesofacial types. There was no difference among gender in brachyfacial types, whereas male predominance was seen in mesofacial and dolichofacial type.